2021
DOI: 10.1111/ner.13278
|View full text |Cite
|
Sign up to set email alerts
|

1.2 kHz High-Frequency Stimulation as a Rescue Therapy in Patients With Chronic Pain Refractory to Conventional Spinal Cord Stimulation

Abstract: Objectives: We aimed to investigate the efficacy of new subperception stimulation paradigms including 1.2 kHz-highfrequency stimulation (HFS) and advanced-HFS field-shaping algorithm (dorsal horn HFS [DHHFS]) in refractory cases which initially benefited from conventional spinal cord stimulation (SCS) and lost the effect throughout time.Materials and Methods: In the context of a rescue-therapy, patients underwent externalization of the implanted SCS-leads and were tested with multiple combinations of new SCS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…Burst stimulation appeared in 2013 [56], paresthesia freehigh frequency techniques were developed contemporarily and it took about 5 years for our community to publish counter-studies, counterbalancing the "overly promising" initial results of some of these techniques [57][58][59][60], the objective being to orient us toward the right compromise for our patients, mixing the two approaches as complementary tools: (i) Spatial resolution can be adjusted by the choice of the neural target and new programing capabilities, based on electrical fragmentation of the current; and (ii) temporal resolution can be adjusted by the IPG, as an alternative to tonic conventional SCS or a combination of several waveforms delivered to the patient, the objective being to enhance our ability to personalize SCS therapies [2,61]. As a consequence, some recently marketed adaptors play on the temporal resolution of SCS and give the patient the opportunity to extensively test the different existing waveforms with promising results [62][63][64]. These new insights need to be integrated in our approach to reflect the state of the art, since this paper's ambition is to propose a salvage algorithm.…”
Section: Methodological Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Burst stimulation appeared in 2013 [56], paresthesia freehigh frequency techniques were developed contemporarily and it took about 5 years for our community to publish counter-studies, counterbalancing the "overly promising" initial results of some of these techniques [57][58][59][60], the objective being to orient us toward the right compromise for our patients, mixing the two approaches as complementary tools: (i) Spatial resolution can be adjusted by the choice of the neural target and new programing capabilities, based on electrical fragmentation of the current; and (ii) temporal resolution can be adjusted by the IPG, as an alternative to tonic conventional SCS or a combination of several waveforms delivered to the patient, the objective being to enhance our ability to personalize SCS therapies [2,61]. As a consequence, some recently marketed adaptors play on the temporal resolution of SCS and give the patient the opportunity to extensively test the different existing waveforms with promising results [62][63][64]. These new insights need to be integrated in our approach to reflect the state of the art, since this paper's ambition is to propose a salvage algorithm.…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…Inspired by the previous algorithm and using a similar substrate, our approach now consists in: (1) checking impedance and hardware dysfunction before (2) attempting to reprogram this patient, using either a spatial and/or a temporal retargeting approach, if the patient is complaining of a loss of coverage, or a temporal resolution retargeting approach, if the patient is complaining of a loss in SCS efficacy, despite adequate back pain coverage, given the possibilities of the IPG and existing lead(s). This approach could require SCS system reexploration and, for some patients, conversion using an implanted adaptor, after a new external lead trial [62,63,[65][66][67].…”
Section: Proposal Of a Salvage Scs Algorithm For Back Pain Componentmentioning
confidence: 99%
“…This first step suggested the potential use of adapters in patients presenting LoE, while preserving the preexisting leads already in place. Similarly, Andrade et al (2021) [35] showed that combination of multiple waveforms Burst and HF, used as a salvage therapy, was safe and efficient to decrease pain in 37 patients already implanted with conventional SCS.…”
Section: Clinical Potential Added Value Of Adapters In Case Of Fscssmentioning
confidence: 97%
“…To take the best decision for the patient, one needs to put into the balance the potential drawbacks of the invasiveness of such procedures, given the risk of infection and total explantation. Second, Internal Pulse Generator (IPG) upgrade; addressing the following question: Should we keep the lead(s) in place and change the way they are programmed [20,35,37]? Indeed, over the last 15 years, new SCS paradigms have been developed, relying on different mechanisms of action [38,39] and offering new ways to shape the electrical field, both spatially and temporally.…”
Section: The Need For Objective Metrics To Characterize Two Fscss Patient Profilesmentioning
confidence: 99%
See 1 more Smart Citation